2011
DOI: 10.1007/s12306-011-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumour of the flexor tendon sheath of the hand: analysis of 27 cases

Abstract: Giant cell tumour of the tendon sheath (GCTTS) is a slowly progressing benign tumour arising from synovial cells of tendon sheaths. It is one of the most common soft tissue tumours in the hand. We report a retrospective study of 27 proven GCTTS of the hand. The mean length of follow-up was 4.5 years (17 months-8.5 years). Radiographic findings are useful and may prove of great diagnostic value. The positive diagnosis was provided by the pathology examination after complete excision that was performed in all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
2
18
1
2
Order By: Relevance
“…In other studies, some differences in term of age distribution were reported, but in many of them, patients were at any age with a peak involvement at third to fifth decades of life (1,5,6,11). Similar to previous studies, our patients were at any age and most of them were in fourth decade of their life (34%).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In other studies, some differences in term of age distribution were reported, but in many of them, patients were at any age with a peak involvement at third to fifth decades of life (1,5,6,11). Similar to previous studies, our patients were at any age and most of them were in fourth decade of their life (34%).…”
Section: Discussionsupporting
confidence: 86%
“…The GCTTS of the hand is a painless slow-growing mass and many patients only complain of a swelling mass more often located at the palmar surface (1,2,4,10,11,14). In current study, none of the patients had explained pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the second most common lesion of the hand and wrist (6,8,9,11). And also, it is the most common soft tissue tumor of the hand and wrist (1,12). Middleton et al defined ultrasonographic appearance of these tumors as hypoechoic and mostly homogenous (11).…”
Section: Discussionmentioning
confidence: 99%